2019
DOI: 10.1186/s12887-019-1451-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of biochemical and haematological changes in dengue fever and dengue hemorrhagic fever in Sri Lankan children: a prospective follow up study

Abstract: Background Series of biochemical and haematological changes occur during the course of dengue infection, which vary depending on the clinical disease. The patterns of change are not well documented and identifying these patterns in children with dengue infection would help to anticipate the progression to different clinical stages thus enabling effective management. Methods A prospective follow up study was conducted during the period of July 2013 – April 2014 at Profes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 8 publications
6
33
0
1
Order By: Relevance
“…Data from Sri Lanka showed that in DHF, serum albumin and cholesterol showed a decline with the increase in the haematocrit. In DHF patients, serum albumin showed a negative correlation with the haematocrit from day 3 to day 6 and was significant on day 4 (r=0.49, p=0.006) and day 4.5 (r=0.41, p=0.022) [25]. The best cut off value of serum albumin to predict entry into critical phase was 37.5 g/L (sensitivity of 86.7%; specificity of 77.8%) [25].…”
Section: Changes In Serum Albumin and Cholesterolmentioning
confidence: 93%
See 4 more Smart Citations
“…Data from Sri Lanka showed that in DHF, serum albumin and cholesterol showed a decline with the increase in the haematocrit. In DHF patients, serum albumin showed a negative correlation with the haematocrit from day 3 to day 6 and was significant on day 4 (r=0.49, p=0.006) and day 4.5 (r=0.41, p=0.022) [25]. The best cut off value of serum albumin to predict entry into critical phase was 37.5 g/L (sensitivity of 86.7%; specificity of 77.8%) [25].…”
Section: Changes In Serum Albumin and Cholesterolmentioning
confidence: 93%
“…Increase in haematocrit closely reflected the decline of the platelet count in both DF and DHF, which was more distinct and rapid in the latter. The highest haematocrit of DHF was seen on day 4, which denotes the onset of the critical phase [25].…”
Section: Haematological Changesmentioning
confidence: 96%
See 3 more Smart Citations